2010
DOI: 10.1021/ma101992c
|View full text |Cite
|
Sign up to set email alerts
|

Self-Diffusion of Polystyrene Solutions in Porous Acrylate-Based Monoliths Studied by 1H PFG NMR

Abstract: The pulsed field gradient (PFG) nuclear magnetic resonance (NMR) method has been used to study the molecular self-diffusion of polystyrene (PS) solutions in porous acrylate-based monoliths. It was found that the characteristic concentration and molar mass dependencies of the PS self-diffusion in the solution (describable by the Zimm and Doi−Edwards models) remain unchanged in case that the self-diffusion occurred in this porous material. However, the self-diffusion coefficients of the PS were reduced in the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 70 publications
(97 reference statements)
2
11
0
Order By: Relevance
“…The clear crossover of the characteristic exponent of −0.5 to higher negative values of the exponents of the molar mass dependence of PS was also verified in refs. . Whereas Beckert et al demonstrated pulsed field gradient measurements in semidilute solutions of PS in deuterated benzene, Zettl et al measured diffusion coefficients with fluorescence correlation spectroscopy of PS in toluene solutions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clear crossover of the characteristic exponent of −0.5 to higher negative values of the exponents of the molar mass dependence of PS was also verified in refs. . Whereas Beckert et al demonstrated pulsed field gradient measurements in semidilute solutions of PS in deuterated benzene, Zettl et al measured diffusion coefficients with fluorescence correlation spectroscopy of PS in toluene solutions.…”
Section: Resultsmentioning
confidence: 99%
“…. Whereas Beckert et al demonstrated pulsed field gradient measurements in semidilute solutions of PS in deuterated benzene, Zettl et al measured diffusion coefficients with fluorescence correlation spectroscopy of PS in toluene solutions. Beckert et al showed the molar mass dependences of PS at different concentrations in deuterated benzene and also obtained different slopes for molar masses below and above 30 000 g mol −1 .…”
Section: Resultsmentioning
confidence: 99%
“…74 Monolithic and silica-based supports were also fabricated via grafting of two polymerizable monomers with carboxylate-containing ligands, exo,exo-7-oxa-2-norbornene-5,6-dicarboxylic anhydride and 7-oxa-2-norbornene-5-carboxylic acid. 20 ROMP-based monolithic supports were synthesized through grafting of either of these two monomers directly with the living ROMP-based termini of the synthesized supports.…”
Section: Supported Catalystsmentioning
confidence: 99%
“…Self-diffusion could be correlated to the reptation of polymer chains by using the Zimm model and the Doi-Edwards model. [83] The other characterization methods for monolithic materials have been described boundlessly, but the basic methods are listed only briefly. The most important tools used for the evaluation of porosity are inverse size-exclusion chromatography (ISEC), mercury intrusion, and Brunauer-EmmettTeller gas adsorption studies.…”
Section: Characterizationmentioning
confidence: 99%